The Impact of Tax Compliance on Future Certainty: A Simulative Artificial Intelligence Modeling of Optimization Portfolios - Muljanto Siladjaja (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2026)
Tax compliance is proven as a quality measurement, indicating the majority probability of achieving future certainty without the possibility of total loss of investment returns, and it is a new indicator of no tax avoidance. Unambiguously, the dividend policy's signaling effect predicts future firm value: management tends to adopt a payout policy with high growth to take advantage of low-cost capital financing, which is associated with lower internal conflict intensity. The concept of the information usefulness of financial reporting has been tested using a multilevel, multiple-data-panel regression with a sample of 154 Indonesian manufacturing listed companies. This model includes a dummy variable reflecting high or low earnings quality as a guideline for highly prospective investment decisions. This statistical testing shows that investors have a favorable view of high compliance, with tax management designed to be more